Methods of Increasing Miscanthus Biomass Yield for Biofuel Production - Evgeny Chupakhin; Olga Babich; Stanislav Sukhikh; Svetlana Ivanova; Ekaterina Budenkova; Olga Kalashnikova; Olga Kriger (Energies, 2021)
The lignocellulosic perennial crop miscanthus, especially Miscanthus × giganteus, is particularly interesting for bioenergy production as it combines high biomass production with low environmental impact. However, there are several varieties that pose a hazard due to susceptibility to disease. This review contains links showing genotype and ecological variability of important characteristics related to yield and biomass composition of miscanthus that may be useful in plant breeding programs to increase bioenergy production. Some clones of Miscanthus × giganteus and Miscanthus sinensis are particularly interesting due to their high biomass production per hectare. Although the compositional requirements for industrial biomass have not been fully defined for the various bioenergy conversion processes, the lignin-rich species Miscanthus × giganteus and Miscanthus sacchariflorus seem to be more suitable for thermochemical conversion processes. At the same time, the species Miscanthus sinensis and some clones of Miscanthus × giganteus with low lignin content are of interest for the biochemical transformation process. The species Miscanthus sacchariflorus is suitable for various bioenergy conversion processes due to its low ash content, so this species is also interesting as a pioneer in breeding programs. Mature miscanthus crops harvested in winter are favored by industrial enterprises to improve efficiency and reduce processing costs. This study can be attributed to other monocotyledonous plants and perennial crops that can be used as feedstock for biofuels.